Oriental Reed Warblers do not abandon Common Cuckoo chicks during prolonged nestling periods - Hanlin Yan; Huahua Zhao; Haixia Luo; Longwu Wang; Laikun Ma; Wei Liang (Avian Research)
The Oriental Reed Warbler (Acrocephalus orientalis) is one of the most commonly used hosts for the parasitic Common Cuckoo (Cuculus canorus). However, as hosts that feed unrelated parasitic nestlings may suffer extra reproductive costs, they may be less willing to care for nestlings that have prolonged nestling periods. To test this hypothesis, the duration of feeding by Oriental Reed Warblers under natural conditions for their own nestlings was compared with the duration of feeding under natural conditions for Common Cuckoo nestlings and for artificially prolonged cuckoo nestlings. The results showed that Oriental Reed Warblers did not starve, drive away, or desert any of the nestlings in the experiment, and neither parent was left alone. Our experimental study indicates that both Oriental Reed Warbler parents were willing to care for nestlings with a prolonged nestling period (up to 30 days, twice the average duration time that the Oriental Reed Warblers fed their own chicks in natural conditions). However, further experiments and observations are required in other host bird species to examine whether both parents or one of the parents may exhibit the behavior of abandoning nestlings with a prolonged nestling period.